Impact of the 50 Hz harmonics on the beam evolution of the Large Hadron Collider - S. Kostoglou; G. Arduini; Y. Papaphilippou; G. Sterbini; L. Intelisano (Physical Review Accelerators and Beams, 2021)
Harmonics of the mains frequency (50 Hz) have been systematically observed in the transverse beam spectrum of the Large Hadron Collider (LHC) since the start of its operation in the form of dipolar excitations. In the presence of strong nonlinearities such as beam-beam interactions, as many of these 50 Hz harmonics reside in the vicinity of the betatron tune they can increase the tune diffusion of the particles in the distribution, leading to proton losses and eventually to a significant reduction of the beam lifetime. The aim of this paper is to determine whether the 50 Hz harmonics have an impact on the beam performance of the LHC. A quantitative characterization of the 50 Hz ripple spectrum present in the operation of the accelerator, together with an understanding of its source is an essential ingredient to also evaluate the impact of the 50 Hz harmonics on the future upgrade of the LHC, the High Luminosity LHC (HL-LHC). To this end, simulations with the single-particle tracking code, sixtrack, are employed including a realistic 50 Hz ripple spectrum as extracted from experimental observations to quantify the impact of such effects in terms of tune diffusion, dynamic aperture, and beam lifetime. The methods and results of the tracking studies are reported and discussed in this paper.